Correlation between NT pro-b-type Natriuretic peptide and left ventricular ejection fraction in children presenting with Dyspnea – a prospective cohort study - Dr. Aswathy Rajan; Dr. Shriyan Ashvij; Dr. Prem Alva; Dr. Santosh T Soans (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Simple screening tests exist for congenital heart diseases but the same cannot be said for cardiac failure in children. Although echocardiography is considered the gold standard for the detection of left ventricular dysfunction, it is relatively expensive and is not often readily available. We aim to prove that NT pro-B-type natriuretic peptide levels may be useful in ruling out the diagnosis of heart failure in children presenting to the emergency room with dyspnea by studying the relation between left ventricular ejection fraction and NT pro-BNP. Methods: Seventy four patients presenting to the emergency department with dyspnea and fulfilling the modified Ross’ criteria for heart failure were included in the study. NT pro-BNP levels were measured for all the patients and a two-dimensional echocardiographic study was performed for them. Statistical analyses were performed using chi square test for independent samples and Pearson correlation tests. Results: A significant inverse correlation was observed between NT pro-BNP levels and left ventricular ejection fraction (r=-0.789, p=0.003). Conclusion: NT pro-BNP assay appears to hold promise as a potent and cost effective test of choice for acutely dyspneic children, which could replace chest x-ray and echocardiography as first investigation in such patients in urgent care settings.